Pengaruh Pupuk Kandang Sapi dan Konsentrasi Urine Kelinci terhadap Pertumbuhan Bibit Kopi Liberoid Meranti - Abdul Halim Luthfi; Santi Rosniawaty; Intan Ratna Dewi Anjarsari; Mira Ariyanti (Paspalum: Jurnal Ilmiah Pertanian, 2023)
Liberoid Meranti coffee seeds can grow well if they are cared for properly. The plant nursery phase determines the successful growth of Liberoid Meranti coffee plants. One of the important maintenance actions carried out when cultivating coffee plants is choosing planting media and fertilization. The organic fertilizer that can be used as a planting media mixture in Liberoid meranti coffee nurseries is cow manure. Rabbit urine is a liquid organic material that contains nutrients, so it can be applied to soil or plants to add nutrients. Liquid organic materials contain macro- and micronutrients. Using the right composition of cow manure and rabbit urine concentrations really determines the growth of Liberoid Meranti coffee plant seeds. This experiment was carried out from February 2023 to June 2023 at the Ciparanje experimental garden, Padjadjaran University, Jatinangor District, Sumedang Regency. This experiment was carried out using a randomized group design (RAK) with nine treatments: soil + 2g urea; soil + 25% rabbit urine; soil + rabbit urine 50%; soil + cow manure (1:1) + rabbit urine 25%; soil + cow manure (1:1) + rabbit urine 50%; soil + cow manure (2:1) + rabbit urine 25%; soil + cow manure (2:1) + rabbit urine 50%; soil + cow manure (3:1) + rabbit urine 50%, and each treatment was repeated three times to obtain 27 experimental units. The experimental results showed that there was an influence of the composition of cow manure as a mixture of planting media and the concentration of rabbit urine on the growth of Liberoid Meranti coffee seedlings, except for the increase in the number of leaves. The composition of a mixture of planting media with cow manure (3:1) and a rabbit urine concentration of 25% provides the best growth for Liberoid Meranti coffee seedlings.